Uncommon Causes of Stroke 2008
DOI: 10.1017/cbo9780511544897.020
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Complications of Fabry’s Disease

Abstract: Fabry's disease (FD) is a rare, sex-linked disorder resulting from a-galactosidase deficiency. Cerebrovascular complications have been reported in the literature but have not been systematically analyzed. We report 2 patients and review 51 previously reported cases (descriptive meta-analysis) to clarify the clinical, radiologic, and pathologic features. The average age at onset of cerebrovascular symptoms was 33.8 years for hemizygous individuals (n = 43) and 40.3 years of heterozygotes (n = 10). The most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
115
2
11

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(134 citation statements)
references
References 86 publications
6
115
2
11
Order By: Relevance
“…Such alterations have been found to be pronounced in cerebral white matter probably because of the arterial supply by long perforating arteries [10]. The posterior cerebral artery territory could also be identified as susceptible for vascular lesions and perfusion disturbances [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such alterations have been found to be pronounced in cerebral white matter probably because of the arterial supply by long perforating arteries [10]. The posterior cerebral artery territory could also be identified as susceptible for vascular lesions and perfusion disturbances [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mutations have been described that account for deficient activity of the enzyme α-galactosidase A [2] leading to progressive accumulation of neutral glycosphingolipids, mainly globotriaosylceramide (Gb 3 ), in various organ systems. Lipid deposits occur preferentially in vascular endothelium and smooth muscle cells leading to tissue ischemia and vessel occlusion [3]. Clinical hallmarks are neuropathic pain, angiokeratoma, hypohidrosis, renal dysfunction, cardiac and cerebral involvement (especially left ventricular hypertrophy and premature stroke) [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Cerebrovascular ischemia in Fabry disease has been largely attributed to the progressive deposition of Gb 3 in vascular endothelium, resulting in both luminal compromise and large-vessel ectasia, giving rise to thrombotic and thromboembolic events. 1,6 Although structural compromise to the cerebral arterial vasculature is believed to play a major role in ischemic events, a review of the literature has shown that cerebral ischemia occurs even in the setting of mild to moderate vascular changes. 6 In addition, heterozygote females, who have conventionally been thought to display a less aggressive form of the disease, have more recently been noted to exhibit a very high recurrence rate of recurrent cerebrovascular events.…”
mentioning
confidence: 99%
“…1,6 Although structural compromise to the cerebral arterial vasculature is believed to play a major role in ischemic events, a review of the literature has shown that cerebral ischemia occurs even in the setting of mild to moderate vascular changes. 6 In addition, heterozygote females, who have conventionally been thought to display a less aggressive form of the disease, have more recently been noted to exhibit a very high recurrence rate of recurrent cerebrovascular events. It has further been noted that both hemizygous and heterozygous patients have a high recurrence rate of intravascular thrombosis including venous thrombophlebitis.…”
mentioning
confidence: 99%